Herbertia guyunusae, a new species of Iridaceae from the grassland ecosystem of Río de La Plata, South America - Paz Deble, Leonardo (Phytotaxa, 2022)
Based on field surveys, study of nomenclatural types and other specimens, and review of literature, it is proposed here the new species Herbertia guyunusae, endemic from humid stony grasslands in south-central Rio Grande do Sul state, Brazil. This work provides a detailed morphological description of the new species, information on geographic distribution, habitat, phenology, conservation status, and a discussion of the main differences with the morphologically most similar species. Herbertia guyunusae differs from Herbertia crosae by its outer tepals porcelain dark-violet colored, with one-celled lipidic trichomes scattered near at the base of the blade, by its inner tepals oblong, and stamens with filaments longer and by its bigger anthers. From H. quareimana the new species can be distinguished by its delicate habit, by its narrowly linear leaves, shorter spathes, much smaller flowers, and narrower and oblong inner tepals. With the description of Herbertia guyunusae the genus now encompasses 12 species, 11 of which occurring in the grassland ecosystem of Río de La Plata, with nine endemics to this region. Illustrations, images, maps, and a key of the species of Herbertia are also supplied.